The Construction of the Representation based on Product, Brand Advertisement, and Cause-related Marketing: Aqua Case - Natalia Widiasari (Institute of Research and Community Outreach - Petra Christian University, 2023)
The study discusses on how Aqua as the product as well as brand and its cause related marketing activities become the source of popular culture. The customer and community as the stakeholder of Aqua create new meaning using the brand and its advertisement. The new meaning is representations of people’s daily life. Product, brand, and the cause-related marketing activities are a top-down communication that controlled by the capitalist. The representations are a bottom-up communication of people who are constructing and reconstructing their everyday life for their own interests.